Availability of phosphorus in defluorinated rock phosphate and bone meal for broiler chickens as assessed by a slope ratio assay - Ketaren, P.P; Silalahi, M; Panggabean, T; Aritondang, D (Indonesian Journal of Animal and Veterinary Sciences, 1998)
An experiment was conducted to determine the availability of P in defluorinated rock phosphate (DRP) and bone meal (TT) using a slope ratio assay (SRA) technique . Ten different diets were fed to 300 day-old broiler chicks for three weeks. Basal diet (RB) was formulated to contain 0.38% total P. DRP, TT and dicalcium phosphate (DCP) diets were each containing three different levels of total P: 0.45, 0.52 and 0.59%: At the end of the experiment, tibia bones were collected for ash determination. The availability of P was determined by SRA using tibia bone ash as the main parameter. The result indicated that the availability ofP in the DRP and TT were 83 .6 and 91 .3%, respectively . Â  Key words : Phosphorus availability, slope ratio assay, broiler